Truth as a Victim: The challenge of anti-trafficking education in the age of Q - Benton, Bond (Anti-trafficking review, 2021)
The QAnon conspiracy threatens anti-trafficking education because of its broad dissemination and focus on a range of myths about trafficking. These myths are rooted in historic and ongoing misinformation about abductions, exploitation, and community threats. This article examines the extent of QAnon’s co-optation of human trafficking discourses and evaluates its connection to trafficking myths, particularly related to gender, race, class, and agency. From this perspective, the article considers how anti-trafficking education can respond to these myths and build a pedagogy in the age of Q